Madrasah Education System And Terrorism: Reality And Misconception - Mohd Arif, Mohd Izzat Amsyar; Abdul Rahman, Nur Hartini; Hanapi, Hisham (International Journal of Educational Best Practices, 2017)
Since the terrorist attacks on September 11, 2001, the Islamic schools known as madrasah have been of increasing interest to analysts and to officials involved in formulating U.S. foreign policy toward the Middle East, Central, and Southeast Asia. Madrasah drew added attention when it became known that several Taliban leaders and Al-Qaeda members had developed radical political views at madrasah in Pakistan, some of which allegedly were built and partially financed through Saudi Arabian sources. These revelations have led to accusations that madrasah promote Islamic extremism and militancy, and are a recruiting ground for terrorism. Others maintain that most of these religious schools have been blamed unfairly for fostering anti-U.S. sentiments and argue that madrasah play an important role in countries where millions of Muslims live in poverty and the educational infrastructure is in decay. This paper aims to study a misconception of the role and functions of Islamic traditional religious schools which have been linked with the activities of terrorism. The study will be specifically focus on practice of the traditional Islamic school, which is locally called as ‘madrasah system’.